A Neutronic Study of A Low-Enriched Uranium-Fueled Microreactor Cooled with A Sodium Heat Pipe System Using The OpenMC Code - Bourenane, A.; Hamidatou, L.; Dougdag, M.; Yahiaoui, M. L. (Atom Indonesia, 2024)
The development of Small Modular Reactors (SMRs) represents a pivotal shift in nuclear technology, emphasizing enhanced safety, efficiency, and adaptability. This study examines Toshiba's MoveluX, an innovative micro-reactor, exemplifying advancements in reactor miniaturization suitable for limited spatial environments and hybridization with other energy sources. In this paper, the performance and safety of the MoveluX are rigorously evaluated using the OpenMC code, with an emphasis on critical parameters such as the effective multiplication coefficient and the reactivity worth of control devices. A 3D model of the given microreactor was built based on Toshiba's designs and features a solid core and a heat pipe cooling system. Preliminary results affirm the model's accuracy, and analysis of the neutron spectrum and flux indicates significant fission occurring in the U-238 isotope. Furthermore, the investigation extends to the thermal aspect within the fuel elements, uncovering a significant power density at the interfaces between fuel and moderator. Overall, this research makes a substantial contribution to the field of microreactor design and optimization.